EU GEOGRAPHICAL INDICATIONS FOR CRAFT AND INDUSTRIAL PRODUCTS. A COMPARATIVE LOOK AT GEOGRAPHICAL INDICATIONS FOR OTHER TYPES OF PRODUCTS - Cristiana BUDILEANU (Challenges of the Knowledge Society)
The geographical indications are part of the intellectual property system, and their importance was proven over time both from consumer protection point of view, but also from business point of view. Since almost the end of 2023 we have a new EU Regulation which regulates the GIs for craft and industrial products at EU level and this paper is proposing to present the final legal framework and the provisions implemented regarding the products that will be object of the protection, the registration, opposition and cancellation procedures, the actions against which the registered GIs are protected, the new role of the EUIPO and other novelty aspects in comparison with (1) the legal provisions under the proposal of the EU Regulation, (2) the existing GIs for other types of products and with (3) the new proposal for GIs for wine, spirit drinks and agricultural products.